The hexosamine biosynthetic pathway rescues lysosomal dysfunction in Parkinson’s disease patient iPSC derived midbrain neurons - Wani, Willayat Y.; Zunke, Friederike; Belur, Nandkishore R.; Mazzulli, Joseph R. (Nature Communications, 2024)
Disrupted glucose metabolism and protein misfolding are key characteristics of age-related neurodegenerative disorders including Parkinson’s disease, however their mechanistic linkage is largely unexplored. The hexosamine biosynthetic pathway utilizes glucose and uridine-5’-triphosphate to generate N-linked glycans required for protein folding in the endoplasmic reticulum. Here we find that Parkinson’s patient midbrain cultures accumulate glucose and uridine-5’-triphosphate, while N-glycan synthesis rates are reduced. Impaired glucose flux occurred by selective reduction of the rate-limiting enzyme, GFPT2, through disrupted signaling between the unfolded protein response and the hexosamine pathway. Failure of the unfolded protein response and reduced N-glycosylation caused immature lysosomal hydrolases to misfold and accumulate, while accelerating glucose flux through the hexosamine pathway rescued hydrolase function and reduced pathological α-synuclein. Our data indicate that the hexosamine pathway integrates glucose metabolism with lysosomal activity, and its failure in Parkinson’s disease occurs by uncoupling of the unfolded protein response-hexosamine pathway axis. These findings offer new methods to restore proteostasis by hexosamine pathway enhancement.
CRIS-Team Scopus Importer:2024-06-28